Osteogenesis potential of different titania nanotubes in oxidative stress microenvironment. (June 2018) - Yu, Yonglin; Shen, Xinkun; Luo, Zhong; Hu, Yan; Li, Menghuan; Ma, Pingping; Ran, Qichun; Dai, Liangliang; He, Ye; Cai, Kaiyong
Abstract: Oxidative stress is commonly existed in bone degenerative disease (osteoarthritis, osteoporosis etc .) and some antioxidants had great potential to enhance osteogenesis. In this study, we aim to investigate the anti-oxidative properties of various TiO2 nanotubes (TNTs) so to screen the desirable size for improved osteogenesis and reveal the underlying molecular mechanism in vitro . Comparing cellular behaviors under normal and oxidative stress conditions, an interesting conclusion was obtained. In normal microenvironment, small TNTs were beneficial for adhesion and proliferation of osteoblasts, but large TNTs greatly increased osteogenic differentiation. However, after H2 O2 (300 μM) treatment (mimicking oxidative stress), only large TNTs samples demonstrated superior cellular behaviors of increased osteoblasts' adhesion, survival and differentiation when comparing with those of native titanium (control). Molecular results revealed that oxidative stress resistance of large nanotubes was closely related to the high expression of integrin α5β1 (ITG α5β1), which further up-regulated the production of anti-apoptotic proteins (p-FAK, p-Akt, p-FoxO3a and Bcl2) and down-regulated the expression of pro-apoptotic protein (Bax). Moreover, we found that Wnt signals (Wnt3a, Wnt5a, Lrp5, Lrp6 and β-catenin) played an important role in promoting osteogenic differentiation of osteoblasts under oxidative condition.